2004
DOI: 10.1093/aob/mch190
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Petal Shape Variation of Primula sieboldii by Elliptic Fourier Descriptors and Principal Component Analysis

Abstract: Within a flower the major source of the symmetrical elements is genotypic and the asymmetrical elements are strongly affected by the environment. With respect to petal area, the contribution of genotypes is also large; it is, however, affected by the macro-environment more notably than is petal shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 18 publications
2
91
1
2
Order By: Relevance
“…The 80 coefficients could be classified into two groups related to symmetrical variation (40 coefficients, hereafter referred to as group A) and asymmetrical variation (40 coefficients, group B) (Iwata et al, 1998;Yoshioka et al, 2004). To summarise the information contained in the coefficients in each group, we performed a PCA based on a variance-covariance matrix.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 80 coefficients could be classified into two groups related to symmetrical variation (40 coefficients, hereafter referred to as group A) and asymmetrical variation (40 coefficients, group B) (Iwata et al, 1998;Yoshioka et al, 2004). To summarise the information contained in the coefficients in each group, we performed a PCA based on a variance-covariance matrix.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that the use of elliptic Fourier descriptors and principal component analysis (EF-PCA) was effective in the quantitative evaluation of P. sieboldii petal shape (Yoshioka et al, 2004). EF-PCA has two major advantages: first, it can detect small variations in shape, and second, it can be used to evaluate the shapes of objects independently of their size.…”
Section: Introductionmentioning
confidence: 99%
“…This software package evaluates contour shapes based on Elliptic Fourier descriptor (EFDs). EFDs have been effectively applied to the analysis of various biological shapes in animals (Rohlf and Archie, 1984;Ferson et al, 1985;Bierbaum and Ferson, 1986;Diaz et al, 1989;Liu et al, 1996;Laurie et al, 1997) and plants (Yoshioka et al, 2004). The SHAPE software contains four programs: ChainCoder, Chc2Nef, PrinComp and PrinPrint (Iwata and Ukai, 2002).…”
Section: Morphometric Analysismentioning
confidence: 99%
“…Kuhl and Giardina [4] introduced in their work a method for shape analysis based on elliptic Fourier descriptors. This method was widely used for shape analysis of plant organs by many researchers [5][6][7]. Mebatsion et al [8] developed an algorithm to classify cereal grains.…”
Section: Introductionmentioning
confidence: 99%